Revisiting carbazole-based polymer donors for efficient and thermally stable polymer solar cells: structural utility of coplanar π-bridged spacers. Issue 17 (29th March 2022) - Kim, Geon-U; Park, Ji-Hyun; Lee, Seungjin; Lee, Dongchan; Lee, Jin-Woo; Jeong, Dahyun; Phan, Tan Ngoc-Lan; Kim, Felix Sunjoo; Cho, Shinuk; Kwon, Soon-Ki; Kim, Yun-Hi; Kim, Bumjoon J.
Abstract : We develop a series of polymer donors containing carbazole-based units (CBT) to achieve high-performance (PCE of 15.54%) and thermally stable PSCs. Abstract : For the realization of highly efficient and thermally stable polymer solar cells (PSCs), we develop a new series of polymer donors (PD s) containing carbazole (Cz)-based units, N -dodecyl-carbazole[3, 4- c :5, 6- c ]bis[1, 2, 5]-thiadiazole (CBT). The coplanar penta-fused-ring structures of the CBT units coupled with π-conjugated bridges (thiophene (T) or thienothiophene (TT)) exhibit highly planar PD conformations that are non-covalently locked by secondary interactions. As a result, the series of PD s ( i.e., P1, P2, and P3) exhibit superior electrical and photovoltaic properties. In particular, the TT–π-bridged PD s, P2 and P3, achieve high power conversion efficiencies (PCEs) of 13.17 and 14.58% when paired with Y6 acceptor, respectively, which outperform the T–π-bridged PD, P1 (10.78%). This result is attributed to the compact intermolecular packing, enhanced crystallinity, and extended conjugation of the PD s featuring TT. Furthermore, an even higher PCE of 15.54% is achieved by a P3-based ternary (P3:Y6:PC71 BM) blend system. This PCE represents the highest among the PCEs of previously reported PSCs featuring Cz-based PD s. In addition, the P3:Y6 blend shows excellent thermal stability by maintaining 90% of its initial PCE after 144 h at 120 °C. Therefore, this study provides important molecular design rules for developing Cz-based PD s and realizing high-performance and thermally stable PSCs.